FACTORS INFLUENCING THE ADOPTION OF CLIMATE-SMART AGRICULTURAL PRACTICES AMONG RICE FARMERS IN BOGORO AND DASS LOCAL GOVERNMENT AREAS, BAUCHI STATE, NIGERIA - Babaji, A.U.; Sunday, G.; Bala, A.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analysed factors influencing the adoption of climate-smart agricultural practices (CSAPs) among rice farmers in Bogoro and Dass Local Government Areas of Bauchi State, Nigeria. Using a multi-stage sampling procedure, 240 farmers were selected, and data were colllected through structured questionnaires and analyzed using descriptive and inferential statistics. Results showed that respondents were predominantly male (55%), married (69.6%), and within the productive age range of 36–45 years. About 42.5% engaged in mixed cropping, while 31.3% and 20.8% attained secondary and OND/NCE education, respectively. Farming experience was considerable, with 45% having 6–10 years, with household size of10–12 members. Regression analysis revealed that education, access to credit, cooperative membership, and annual income (p < 0.001) positively influenced adoption, whereas farm size (p < 0.01) and sex (p < 0.05) were negative predictors. Key constraints included inadequate extension services, high seed costs, and environmental challenges such as drought and rainfall shortages were ranked 1st, 2nd and 3rd respectively. The study concludes that adoption of CSAPs in the area is shaped by both socio-economic and institutional factors but constrained by weak extension delivery, high input costs, and policy gaps. The study recommends the Federal Ministry of Agriculture and Food Security, through State ADPs, to strengthen extension services by training and deploying more agents equipped with digital tools to support rice farmers in adopting CSAPs.